Water-Energy-Food Nexus : A Platform for Implementing the Sustainable Development Goals - Stephan, Raya; Mohtar, Rabi H.; Daher, Bassel; Embid, Antonio; Hillers, Astrid; Ganter, Carl; Karlberg, Louise; Martin, Liber; Nairiz, Saeed; Rodriguez, Diego J.; Sarni, Will (Taylor and Francis, 2018)
This article was developed as an outcome of the “Water-Energy-Food Nexus” High Level Panel (HLP) which took place at the XVI World Water Congress, Cancun Mexico, June 1, 2017. The HLP’s goal was to demonstrate the extent of interconnection between the water, energy, and food Sustainable Development Goals (SDGs) of the United Nations. The HLP highlighted lessons learned from various thematic and regional case studies and experiences. The panel focused on exploring the possible trade-offs among possible pathways for implementation of the SDGs, and on identifying holistic assessment criteria for accounting for potential competition of multiple implementation plans at different scales. This focus led to substantial discussion about ways to improve policy coherence through improved communication between policy and science across both sectors and scales.